Larval development of the western school prawn Metapenaeus dalli Racek, 1957 (Crustacea: Decapoda: Penaeidae) reared in the laboratory. Issue 27 (25th July 2016) - Crisp, Jason A.; Tweedley, James R.; D'Souza, Frances M. L.; Partridge, Gavin J.; Moheimani, Navid R.
ABSTRACT: The six Naupliar, three Protozoea, three Mysis and first post-larval forms of the western school prawn Metapenaeus dalli Racek, 1957 were cultured in the laboratory. These stages were described in detail and compared to those of other metapenaeids. The ontogenetic development occurred in 12 days at 26°C, with both the growth rate and morphological patterns of development in M. dalli broadly following those recorded for other metapenaeids. Differences were found between M. dalli and other metapenaeids at corresponding stages of larval development, with these being the number, location and composition of individual setae and other minor spinal development.